Impact of physicians' clinical experience and workplace on patients' care of urticaria in Japan: A sub‐analysis of a nation‐wide cross‐sectional web questionnaire survey - Shunsuke Takahagi; Akiko Kamegashira; Naoko Inomata; Atsushi Fukunaga; Takeshi Nakahara; Koremasa Hayama; Michihiro Hide (Journal of Cutaneous Immunology and Allergy, 2022)
We previously reported results of a web‐based questionnaire conducted to better understand real‐world clinical management of urticaria and angioedema. We here described a sub‐analysis of the data with stratification by the type of participants’ workplaces and the length of their clinical experience of dermatology. This study revealed that treatments and examinations for urticaria and angioedema are affected by length of experience and type of physicians’ workplaces to manage the diseases.